The Implementation of Marketing Strategies in the Eco-friendly Business "Artani Bulk Store" - Muh Irsyad Abror Putra Raja Akbar; Hery Maulana Arif; Sitti Mutmadania; Eka Astria; Andi Yusril Yasmun (PINISI Discretion Review, 2023)
In the world of research, it has been widely proven that the fashion industry also contributes to global carbon emissions and can consume up to 216 trillion liters of water just for various t-shirts. Despite this, people are now seeking new alternatives to meet their daily needs while preserving the environment. Ecofriendly products have emerged as the answer, not only for business purposes but also as environmental heroes. Several data collection techniques were employed by the researcher, including observation, interviews, and direct field surveys. Ria, the founder of Artani Bulk Store, began with her experience of providing baby food for her 6-month-old child. She faced difficulties in buying baby food ingredients in small quantities. Artani Bulk Store is an example of a business that focuses not only on profit but also on environmental and community concerns. They have the strength and opportunities to grow, but they also face competitive challenges. Their marketing strategy revolves around a green marketing approach and product transparency, with the aim of building awareness and connecting with environmentally-conscious consumers.